"Influence of diet on mood and social cognition: a pilot study". Issue 9 (10th September 2020) - Ugartemendia, L.; Bravo, R.; Castaño, M. Y.; Cubero, J.; Zamoscik, V.; Kirsch, P.; Rodríguez, A. B.; Reuter, M.
Abstract : Diet, mood & social cognition. Abstract : Recently, a relationship has been observed between nutrition and social cognition. In this aspect, several dietary patterns, or even some probiotics, have been reported as social cognition modulators. However, to date, no studies have reported the effects of specific nutrients. Our aim was to evaluate the relationship between dietary macronutrients and the processing of social and affective information. Participants were undergraduates from the University of Extremadura (Badajoz, Spain) aged 21.3 ± 2.9 years., with a BMI of 22.8 ± 3.9 (kg m −2 ). The students' social cognition and diet were analysed through questionnaires and a dietary record. The diets were analysed with DIAL v.1.18® software (Alce Ingeniería®). The participants filled out the WHO-5 well-being index, Beck's anxiety inventory, Beck's depression inventory, ruminative response scale (RSS), Leiden index of depression sensitivity (LEIDS-r), empathy quotient (EQ), and interpersonal reactivity index (IRI). To analyse the data, nutrients were grouped through principal component analysis (PCA) into lipids, carbohydrates and proteins. Additionally, we assayed if these principal components were associated with psychological questionnaire scores using multiple linear regression analyses. The dietary pattern differed from the traditional Mediterranean diet due to high intake of proteins and saturated fatty acids. Regarding social cognition and macronutrients, we found a positive association between lipids, specifically cholesterol, and the Perspective-Taking Scale (an IRI component). Carbohydrates influenced the RSS, indicating that complex carbohydrates may be a risk factor for depression. Moreover, the brooding factor, a component of the RRS, was negatively affected by dietary carbohydrates and proteins, specifically by fiber and aspartate. Diet may influence several variables related to social cognition and mood. Particularly, a low-cholesterol diet rich in fiber, complex carbohydrates, and aspartate apparently provides benefits, improving the processing of social and affective information and psychic well-being.